Exploring the physical and mental health of high-speed rail commuters: Suzhou-Shanghai inter-city commuting. (September 2020) - Wang, Lan; Zhang, Surong; Sun, Wenyao; Chen, Chia-Lin
Abstract: Introduction: High-speed rail (HSR), with its remarkable time-space shrinkage, has potentially enlarged labour market catchment areas and encouraged inter-city commuting; much literature, however, links long-distance commutes with health risks. Methods: This study develops a conceptual framework in which a set of HSR-informed independent variables (shift in long-commute modes, transfer modes and travel time to and from HSR stations, job prospects and living conditions, and socio-economic attributes) are explored to discern physical and mental health variations. Ordinal logistic regression models are used to analyse 288 questionnaire samples from a cross-sectional study of HSR commuters travelling between Suzhou and Shanghai, China. Results: Gaining insight into factors associated with HSR commuters' physical and mental health, the findings from descriptive analyses reveal a slightly negative association. While travel-related instrumental factors (shift long commute from non-HSR to HSR, active transfer modes, shorter travel times to and from HSR stations) and noninstrumental factors (intimate family and social relationships) show significantly positive health benefits, commuters, such as technicians and professionals, with low rent/mortgage levels (implying lower quality of residence and relative inability to afford home ownership), report significantly negative associations with their health. Conclusion: This paper concludes that HSR commuting requires personal commitment and a healthy work/life balance. Association with physical and mental health reflects a combination of structural inequality and personal travel experiences and living conditions. To promote the health of HSR commuters, a coordinated spatial-economic strategy at the mega-city regional level should be implemented to improve distribution of employment opportunities and consider users' perspectives on long-distance commuting, taking a holistic approach to door-to-door travel, infrastructure provision, and services operation. Highlights: A conceptual framework exploring multifaceted factors underlying HSR commuting and health. Slightly negative association with physical and mental health unveiling struggles between work and life balance. Structural inequality, personal travel experiences and living conditions associate with HSR commuters' health. A coordinated spatial-economic strategy at the mega city-regional level is critical to promote HSR commuters' health. Shedding light on health promotion interventions, not only in China but wherever HSR has been implemented.